1959
DOI: 10.1139/v59-215
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of Methyl Radicals With Formaldehyde

Abstract: The pyrolysis of di-t-butyl peroxide has been reinvestigated and used as a source of methyl radicals to study the abstraction reaction between methyl radicals and formaldehyde. At low [IHCIlO]/[peroxidc] ratios the system was simple enough for kinetic analysis, and a value of 6.6 Iccal/mole was obtained for the activation energy. At higher [HCHOl/[peroxide] ratios the system became very complicated, possibly due to the increased inlportance of addition reactions. INTRODUCTIONThe reaction between methyl radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

1961
1961
2013
2013

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 12 publications
(8 reference statements)
2
16
0
Order By: Relevance
“…apart from ethane >> rnetl~ane > ethylene no other significant products were found, in agreement with earlier studies (3,6,8,11).…”
Section: Materials and Experimental Techniquesupporting
confidence: 92%
See 1 more Smart Citation
“…apart from ethane >> rnetl~ane > ethylene no other significant products were found, in agreement with earlier studies (3,6,8,11).…”
Section: Materials and Experimental Techniquesupporting
confidence: 92%
“…At small percentage conversions, the rate of formation of acetone can be used as a measure of the rate of decomposition of the peroxide (3,11). Thus, since it was not in general possible to transfer the whole contents of the reaction vessel to the vapor phase chromatographic (v.p.c.)…”
Section: Materials and Experimental Techniquementioning
confidence: 99%
“…deter~nined by equation [2] varies with the isobutane pressure, which coilfirnls the earlier observation (1). Unlilce the addition of hydrogen (2), however, the addition of isobutane to acetone-dG did not affect the ratio IIcD1/R&yD6[A] in any way.…”
Section: E X P E R I M E N T a Lsupporting
confidence: 83%
“…Multiplying, one obtains Ic,k,,,-1i2, the quotient determined at lower temperatures in previous work (4,5).…”
mentioning
confidence: 91%
“…Including literature data from 357-1005 K, the Arrhenius plot for this quotient is a curve. The reaction of methyl radicals with formaldehyde [9] CH, + CHzO -+ CH, + CHO has one of the smallest activation energies known for The radicals formed in reactions 3, and decomtransfer Of a from a atom to pose rapidly to form CH,O; the radical formed in a methyl radical (1) Recent experiments, using CH, reaction decomposes to form CO. and CH2O generated in the P Y~~~Y~~~ Of diMaking the steady-stafe assumption for each ether at to 1223 (2) and loo' (3)7 radical, assuming long chains and integrating the have indicated that the reaction is faster at these rate equations for product formation, tile following temperatures than predicted from Arrhenius parameters determined at 357-435 K (4,5 actions, have been omitted. The assumptions will be reconsidered in the Discussion.…”
mentioning
confidence: 99%